Dampak Model Pembelajaran Kooperatif Think, Pair and Share (TPS) Terhadap Hasil Belajar Matematika Siswa Kelas VII SMP PGRI 3 Larangan Kota Tangerang - Jannah, Miftahul; Somawati, Somawati (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to determine the impact of the Think Pair and Share (TPS) cooperative learning model on the mathematics learning outcomes of Grade VII junior high school students at PGRI 3 Larangan Junior High School, Tangerang City. This type of research is a pseudo-experiment using a purposive sampling technique. The data collection technique used is a test technique. The collected data was analyzed using a t-test with a significance level of α = 0.05. Based on the results of data analysis, it is known that the calculation of the t-test post-test can be concluded that t calculates > t table, which is 2.281 > 1.67 which has an impact on the mathematics learning outcomes of students given the TPS learning model. This shows that the learning outcomes of the TPS learning model are higher than the Student Team Achievement Devision (STAD) learning model.